A Rare Case of Biliary Atresia with Biliary Ascites on a (Hepatobiliary Iminodiacetic Acid) HIDA Scan - Loyal, Poonamjeet Kaur; Makhdomi, Khalid; Gitau, Samuel (World Journal of Nuclear Medicine, 2024)
Biliary atresia is one of the most challenging conditions in pediatric surgery even when it is the only finding. Here we present a rare case of biliary atresia complicated with biliary ascites due to ductal perforation identified on a hepatobiliary iminodiacetic acid (HIDA) scan.
Keywords: Biliary atresia; biliary ascites; HIDA